Respuesta :

Let x = first number
Let y = second number
x + y = 4
x * y = (-12)
Solve the first equation for x.
x = 4 - y
Now substitute this value of x into the second equation.
(4 - y) * y = (-12)
4y - y² = (-12)
y² - 4y - 12 = 0
(y + 2) * (y - 6) = 0
Now set both polynomials equal to zero
y + 2 = 0
y = -2
y - 6 = 0
y = 6
If you substituted these two values for y into either equation and solve for x, you would get the combination of 6 and -2

Hope I was able to help you! :)
6 and -2. When you add -2+6, you get 4. And when you multiple -2*6 you get -12
Hope this helps!